Political Participation and Socioeconomic Status (SES) the Governor Election in Kepulauan Riau - Mirza Ayunda Pratiwi; Rizqi Apriani Putri; Mahadiansar Mahadiansar (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Political participation is an individual activity that may affect a country's or government's political policy. Political participation in democracy takes many forms, such as voting, establishing a political group, engaging in legal or illegal protests, campaign involvement, discussing politics offline or online, or becoming a political party member. The term political participation in this study refers to voting participation. Voter participation is important because it creates a political and democratic climate that encourages people to participate actively in state administration. To determine strategies and policies to increase voter participation, what factors can influence someone to vote can be seen. One factor that influences a person's desire to participate in politics is a person's socioeconomic status. Therefore, this study examines how Socioeconomic Status (SES) influences political participation. Political participation in this study is seen from whether the permanent voters (DPT) exercise their right to vote in the 2020 gubernatorial election. The SES consists of socioeconomic status, which is seen from: demographic background (social status, including age, ethnicity, educational background, and religion); economic status of the average income of voters per month. Krejcie Morgan sampling method, 384 respondents were processed with Eviews 11 software using logit regression model analysis. This study found three variables significantly affect the dependent variable: Ethnic, residential election participation, and trust level in the candidate. This study recommends that the strategies used in the efforts to enhance political participation of the Riau Islands community in the regional head election are: forming volunteers democracy, dividing four segments of socialization, improving the quality of the organizing committee resources by conducting technical guidance, aggressively achieving political socialization, political publications, and the delivery of the stages of the elections using various social media platform. Moreover, implementing Good Governance will produce output from society's most economical market mechanisms. Thus, it is expected that people's political awareness will be enhanced.